THE SELF-MEANING BUILT BY JOURNALIST IN BANTEN PROVINCE IN SPREADING HATE SPEECH IN THE PRESIDENTIAL ELECTION 2019 - Liza Diniarizky Putri; Annisarizki Annisarizki; Dicky Andika (ASPIRATION Journal, 2020)
The current mass media industry is not the only sovereign of the source of informations. Based on technological advancements, social media exists as a blurring medium for space and time constraints in disseminating and exchanging information, but the minimal control mechanism causes content on social media is not only be positive, but also can be negative such as the spread of hate speech. Hate speech also enlivening journalist's Facebook accounts in Banten, especially during the 2019 Presidential Election campaign which tends to be a "new weapon" of social movements. This research was conducted with qualitative research methods through a phenomenological research approach. By using Social Construction Theory as a frame of qualitative analysis, it was revealed that the journalists who spread hate speech through social media Facebook interpret themselves as agents of change who do not want Indonesia to be led by the wrong leader.